The significance of microfinance to Pototan rice farmers in the Philippines: An analysis - Gutierrez, Mikaela Luis A. (Animo Repository, 2022)
This study investigates microfinance's influence on rice farmers in Pototan, Iloilo. The research examined the impacts of different loan amounts on rice yield and COVID-19's impact on the profitability of Pototan rice producers. The research paper employed a quantitative causal design. It adopted purposive sampling, with 40 rice farmers who were active in cooperatives serving as respondents. Using surveys and unstructured interviews, data was obtained. The study hypothesized that farmers who took out greater loans would have better crop yields. Results indicated that loan amount boosts rice farmer production. Raising loan amounts in thousands increases farmers' estimated production by 4.60 or 4 to 6 sacks of rice (each sack at 50 kgs standard). Each additional 1,000 pesos loaned diminishes profitability by 400 pesos. The efficiency of input consumption, such as farmland acreage, seeds sowed, and fertilizer used, adds equally to yield and profitability whether farmers take out loans or not. The profitability model generated a negative coefficient, but the variability is too considerable for a conclusive comment. Future studies may need a more extended data set or more farmers to precisely pinpoint this effect. During the COVID-19 epidemic in Pototan, Iloilo, rice farming and production had minimal to no change in profitability and productivity. Due to lockdown measures and strict health procedures, farmers' indebtedness only significantly grew during the pandemic. The size of the land influences rice yield as much as the loan amount, according to Pototan's data.